Wondrous transformations a maverick physician, the science of hormones, and the birth of the transgender revolution - Li, Alison, 1963- (The University of North Carolina Press, 2023)
"Harry Benjamin (1885-1986), a German-born endocrinologist, was an early pioneer in hormone therapy and transgender medicine. During his long career, he assisted many people in transitioning, including Christine Jorgensen, the 1950's 'Ex-GI' turned 'Blond Bombshell' media sensation. The two became close collaborators, with Jorgensen working with Benjamin on his influential book The Transsexual Phenomenon, published in 1966. Alison Li's much-needed biography of Benjamin chronicles his passion for hormones and his lifelong interest in sexology. Drawn from extensive research in archival documents, secondary sources, and interviews, Li tells the story of Benjamin's collaborative work with over a thousand transgender patients and his efforts in education, research, and networking, helped to create the institutional foundations of transgender medicine"--